Implementasi Praja Sakti (Pelayanan Bersama Jemput Dan Bergerak Dalam Sistem Adminstrasi) Dalam Peningkatan Kualitas Pelayanan Publik Kecamatan Kuta Selatan Kabupaten Badung Bali - Cahya, Vanessa Dwi; Sunarya, Aris (Soetomo Magister Ilmu Administrasi, 2024)
In order to enhance the quality of public services at the district level, ongoing innovations are being developed by the district government. Kuta Selatan is one of the areas that has been advancing innovation in public services, known as PRAJA SAKTI. This research aims to explain the impact and challenges experienced in the implementation of the PRAJA SAKTI program for improving public services. Interviews were conducted as the method for data collection, involving the PRAJA SAKTI team as the key informants. The questions posed were developed based on indicators from G.C. Edward III, encompassing communication, resources, decision-making, and bureaucratic structure in public services. The findings from the research indicate that the PRAJA SAKTI program can enhance public trust in the government. The community perceives that the government is committed to providing better and easily accessible public services, leading them to feel more valued and recognized by the government. On the other hand, obstacles encountered in the implementation of the PRAJA SAKTI program include the limited resources of the organizing team. Due to these constraints, PRAJA SAKTI has not been implemented simultaneously. Overall, the PRAJA SAKTI program has a positive impact on the community but faces challenges in its execution.